Analisis Pemecahan Masalah Geometri Bidang Datar dalam Konteks Lokal dan Tingkat Pemahaman Siswa Kelas XI-7 SMA Negeri 3 Medan pada Materi Segitiga - Pujiono Sihite; Immanuel Simbolon; Samuel Tappin Martua Sitorus; Joyce Lidya Patricia Daeli; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students' problem-solving abilities in plane geometry within a local context and to identify types of human errors made by Grade XI-7 students at SMA Negeri 3 Medan on triangle material. The studyemployed a descriptive qualitative approach with 20 students selected through purposive sampling. Data were collectedthrough a written test consisting of 5 Higher Order Thinking Skills (HOTS) essay questions based on local contexts, completed within 40 minutes, and analyzed using a human error analysis scoring rubric. The results indicate that students' understanding levels vary across indicators: translation, interpolation, and extrapolation. The dominant error types identified include conceptual errors, procedural errors, and careless errors. These findings have important implications for mathematics teachers in designing more contextual geometry learning based on student error analysis.